The effect of glysemic control on myocardial performance index in patients with type 2 diabetes mellitus [Tip 2 diyabetli hastalarda glisemik kontrolün miyokard performans ýndeksine etkisi] - (:unkn) unknown (My University, 2011)
Purpose: Type 2 diabetes mellitus (DM) and poor glucometabolic control increase the risk of developing the heart failure. We aimed to investigate association between glysemic control and left ventricle myocardial performance index (MPI) in patients with type 2 DM and without known cardiac disease. Material and Method: Left ventricular functions using conventional transtorasic and tissue doppler echocardiography were evaluated in 42 patients. Glysemic control is expressed as fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c). The exclusion criteria were known cardiovascular system diseases, pulmonary diseases, endocrine diseases; anemia, history of angina pectoris, dyspnea, and peripheral edema. Results: Fourty two patients, men (40.5%) and women (59.5%) aged 37-57 years were included. There was no correlation between HbA1c and MPI, and FPG and MPI. Moreover, there was no correlation between glysemic control and ejection fraction (EF). Conclusion: It was shown that ventricular abnormalities in diabetics without known heart disease and also elevated fasting glucose level are associated with risk of congestive heart failure. The Doppler index, MPI, allows both sistolic and diastolic performance to be estimated. In our study, left ventricular functions were similar between healthy controls and diabetics without known cardiac disease. We could not find any relationship between glysemic control and left ventricular dysfunction expressed by EF and MPI.
Keywords: Diabetes mellitus; Hemoglobine A1c protein; Human; Type 2